Continuous Integration (CI) and Continuous Delivery (CD) - A Practical Guide to Designing and Developing Pipelines - van Merode, Henry (Apress, an imprint of Springer Nature, 2023)
Use continuous Integration (CI) and continuous delivery (CD) to improve the speed of software delivery. This book presents a game changer-how to use pipelines to automate the software delivery process. The theories about CI/CD are much the same, but the book covers what the development of pipelines looks like and how testing of pipelines themselves should be performed. Most teams just plunge into coding, without thinking about the CI/CD process itself. Why don't we use the same development method for pipelines that we use for apps?Pipelines code development undergoes similar stages as application code development, such as requirements analysis, development, testing, implementation, operations, and monitoring. This is the starting point of the book. It describes the current challenges with pipeline development and how this process can be improved and structured. It describes in detail how to design pipelines and shows examples in BPMN 2.0 notation.